Immunological Studies of Y Protein. A MAJOR CYTOPLASMIC ORGANIC ANION-BINDING PROTEIN IN RAT LIVER - Fleischner, Gerald (1972)
An antibody produced against rat Y protein, the major cytoplasmic organic anion-binding protein in liver, was characterized. The antibody precipitated Y protein from liver supernatant fractions and specifically removed the organic anion-binding capacity from this fraction. Y protein was detected by immunodiffusion with this antibody in the supernates of rat liver, kidney, and small intestinal mucosa and was not detected in supernates of 16 other tissues including bile and serum. Precipitation with anti-Y was not detected with supernates of liver from 20 other species, including man. Quantitative radial immunodiffusion revealed Y protein to constitute 4.5% of supernatant protein in rat liver and approximately 2% of supernatant protein in rat kidney and small intestinal mucosa. Phenobarbital administration increased the concentration of Y protein in rat liver by 280%, but not in kidney or small intestinal mucosa, and was associated with increased plasma disappearance of sulfobromphthalein sodium, indocyanine green, and bilirubin, and increased hepatic, but not kidney or small intestinal mucosal, content of these organic anions. These observations provide further evidence indicating that the concentration of Y protein is a major determinant of organic anion flux across the plasma membrane of the liver cell. Immunodiffusion and immunoelectrophoresis revealed serological identity between Y protein, cortisol metabolite-binding protein I. and the major azocarcinogen-binding protein.